Plant Organelle DNA Maintenance - Nielsen, Brent L.; Ahmad, Niaz (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book provides reviews and primary research articles that discuss the replication, repair, maintenance, and structures of plant organelle genomes. Rearrangements of these genomes are common and provide a way to distinguish closely related plant species. Some articles in the book discuss recent advances in identifying specific proteins and potential mechanisms involved in DNA replication, recombination, and repair in plant mitochondria and chloroplasts.